Effect of a regular consumption of traditional and roasted oat and barley flakes on blood lipids and glucose metabolism–A randomized crossover trial - Reiners, Sarah; Hebestreit, Sandra; Wedekind, Lisa; Kiehntopf, Michael; Klink, Anne; Rummler, Silke; Glei, Michael; Lorkowski, Stefan; Schlörmann, Wiebke; Dawczynski, Christine (Frontiers in Nutrition, 2023)
Background: Regular consumption of the soluble dietary fiber β-glucan is associated with decreased total cholesterol (TC), low-density lipoprotein (LDL) cholesterol and blood glucose. Barley and oat flakes as natural sources of β-glucan were roasted to improve sensory quality. The aim of this study was to investigate whether roasting of barley and oat flakes changes the physiological impact of the β-glucan-rich flakes on glucose and lipid metabolism. Method: A five-armed randomized crossover trial design was used. The intervention study was conducted from May 2018 to May 2019 and included 32 healthy subjects with moderately increased LDL cholesterol (≥ 2.5 mmol/L). During the three-week intervention periods, 80 g of roasted or traditional barley or oat flakes, or four slices of white toast bread per day were consumed for breakfast. At the start and the end of each intervention, fasting and postprandial blood was taken. The intervention periods were separated by three-week wash-out periods. Results: During the interventions with the cereal flakes, TC and LDL cholesterol concentrations were significantly reduced compared to baseline values by mean differences of 0.27–0.33 mmol/L and 0.21–0.30 mmol/L, respectively (p < 0.05), while high-density lipoprotein (HDL) cholesterol was only less reduced after the intervention with barley flakes (p < 0.05)by mean differences of 0.03 – 0.11 mmol/L. After the intervention period with toast, TC and HDL cholesterol increased (p < 0.05). The fasting levels of triglycerides, fasting blood glucose and insulin did not change in any group. The effects of traditional and roasted varieties on blood lipids did not differ between the groups. Conclusion: The regular consumption of traditional or roasted barley and oat flakes contributes to the management of cardiovascular diseases by improving TC and LDL cholesterol. Clinical trial registration: https://clinicaltrials.gov/ct2/show/NCT03648112, identifier: NCT03648112.